Tafenoquine exhibits broad spectrum antifungal activity at clinically relevant concentrations in vitro and decreases lung fungal burden in an invasive pulmonary model of Rhizopus in vivo. (January 2022) - Dow, G.; Smith, B.
Abstract: Background: Tafenoquine is active against a broad range of pathogens and accumulates extensively in the lung. We profiled the susceptibility of fungal pathogens to tafenoquine in vitro and in vivo. Methods: Minimum inhibitory concentrations [MICs] of medically important fungal pathogens were determined using conventional in vitro assays. The daily maximum tolerated dose [MTD] of tafenoquine was determined in neutropenic mice and the effect of two doses of tafenoquine [MTD and 0.5xMTD] on survival and fungal burden were assessed in Rhizopus and Aspergillus lung infections models. Results: Mean MICS against panels of yeasts and dimorphic/filamentous fungi were 4.5 and 8.3 ug/mL. The MTD of tafenoquine was 5 mg/kg/day. Against Aspergillus [MIC 16 ug/mL], tafenoquine did not increase survival or decrease fungal burden. Against Rhizopus, [MIC 4 ug/mL], tafenoquine decreased lung fungal burden [by 0.5 logs, P  < 0.05 at the MTD] in a dose-related manner. Survival in the high-dose [MTD] tafenoquine group was 30% whereas it was 0% in the vehicle group and in most legacy studies. Conclusions: Tafenoquine exhibited broad spectrum activity against medically important yeasts and fungi in vitro and a dose-related antifungal effect in a Rhizopus lung infection model at clinically relevant doses.